I think the antiderivative of 3^x should be 3^x/ln(3) not ln(x), right?
As far as why....if I show that [3^x/ln(3)]' = 3^x, will that be enough?
y = 3^x/ln(3)
Take the natural log of both sides, and simplify using log rules:
ln y = ln (3^x/ln(3)) = ln(3^x) - ln(3) = xln(3) - ln(3) = ln(3)(x - 1)
Differentiate implicitly:
1/y y' = ln(3)(1)
y' = ln(3)y = ln(3)[3^x/ln(3)] = 3^x
Since we took the derivative of 3^x/ln(3) and got 3^x, the antiderivative of 3^x must be 3^x/ln(3).
2007-01-17 11:04:51
·
answer #1
·
answered by Jim Burnell 6
·
0⤊
0⤋
Can you explain why the anti derivative of 3^x is 3^x/lnx?
The anti derivative (integral) of 3^x should be 3^x/ln3.
It is because
(d/dx) ( 3^x/ ln3)= (1/ln3) (d/dx) ( 3^x)
=(1/ln3) 3^x* ln 3
= 3^x
2007-01-17 19:20:10
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
You can rewrite x as e^ln(x). So another way to write 3^x is as e^ln(3^x). This is also e^(x*ln(3)). If you integrate this and use the chain rule in reverse, you should wind up with the answer.
2007-01-17 19:18:13
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
Given a to be a constant, a^x = exp(x ln (a)), where exp x means e^x.
Hope this helps, as this should be enough!
2007-01-17 19:16:46
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Just differentiate (3^x)/ln3, and see what you get.
2007-01-17 19:10:42
·
answer #5
·
answered by acafrao341 5
·
0⤊
0⤋